SINTESIS LAKTOGENIN DARI TETRAHIDROFURAN-3-KARBOKSALDEHIDA DAN 2-ASETIL-?-BUTIROLAKTON DENGAN KATALIS NATRIUM METOKSIDA - Jeffy Julianus; Laurensius Widi Andhika Putra (Sanata Dharma University, 2013)
Abstract: Acetogenin compound known for its activity as anticancer by inhibited the NADHubiquinone reductase contained in the mitochondria. These compounds with high liphophilicityproperties have a weakness in solubility with log P 8.44, so modifications to improve thesolubility by maintaining a core group of tetrahydrofuran and ?-lactone as well as shortening thealkyl chain is needed. The modified compounds was lactogenin or 3-(3- (tetrahydrofuran-3-yl)acryloyl) dihydrofuran-2(3H)-one) that have a log P 0.90 and is expected to have a bettersolubility properties than acetogenin. Lactogenin synthesis was based on cross-aldolcondensation reaction by reacting tetrahyrdofuran-3-carbaldehyde and 2-acetyl-?-butyrolactone using sodium methoxide as catalyst. The synthesized compounds were red solutionwith specific smell. The TLC result showed the new products at Rf 0.314. The purity test by gaschromatography showed 74.07% purity. The structure elucidation by infrared and massspectroscopy showed that the synthesized compound was ?-hydroxy lactogenin or 3-(3-hydroxy-3-(tetrahydrofuran-3-yl) propanoyl) dihydrofuran-2(3H)-one.Keywords: NADH-ubiquinone oksidoreduktase, lactogenin, cross-aldol condensationreaction, ?-hydroxy lactogenin